2022
DOI: 10.1109/lpt.2022.3189950
|View full text |Cite
|
Sign up to set email alerts
|

Low-Phase-Noise Tenfold Frequency Multiplication Based on Integrated Optical Frequency Combs

Abstract: We experimentally demonstrate a low-phase-noise tenfold frequency multiplier based on a compact integrated optical frequency comb (OFC) generator. The Indium Phosphide (InP) monolithically integrated OFC is based on a flexible scheme using cascaded optical modulators. The extremely compact frequency multiplier is broadly tunable in wavelength and in OFC repetition frequency, making it interesting for high-spectralpurity mm-waves applications. OFC generation with a 2.6 GHz spacing and 19 tones within a 10 dB po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Against the signal core and its driving source, the comb exhibited expansion of the phase noise in the region below 30 kHz. This is an anticipated effect from the beating product and the phase noise of the o-comb in (3) and ( 4), that is in the optical domain, the near-carrier phase noise of the nth o-comb line is expanded by approximately n times, similar to a behavior of a frequency multiplier [14].…”
Section: B Measured Phase Noise With Different Fiber Lengthsmentioning
confidence: 96%
See 1 more Smart Citation
“…Against the signal core and its driving source, the comb exhibited expansion of the phase noise in the region below 30 kHz. This is an anticipated effect from the beating product and the phase noise of the o-comb in (3) and ( 4), that is in the optical domain, the near-carrier phase noise of the nth o-comb line is expanded by approximately n times, similar to a behavior of a frequency multiplier [14].…”
Section: B Measured Phase Noise With Different Fiber Lengthsmentioning
confidence: 96%
“…Using a photodiode (PD), the o-comb is subsequently converted to the corresponding electrical comb (e-comb) for source extraction. The generation of the o-comb can either be done locally (at the mm-wave TXs or RXs site, et al [14] demonstrated an integrated solution) or distributed through optical fiber to multiple locations, as already demonstrated with 22 km of standard single-mode fibers (SSMFs) and compared against commercially available oscillator solution [11]. In addition, the method to synchronize between the TXs or RXs with access to the comb and the corresponding remote RXs or TXs was also demonstrated by broadcasting one of the lower frequency tones, from the e-comb, at 6.25-GHz over-the-air, thus eliminating the need for the TX-RX clock synchronization via global positioning system (GPS) or other means [15], [16], further reducing the carrier recovery requirement and the complexity thereof.…”
mentioning
confidence: 99%
“…The output carrier frequency is widely tunable, being defined by the difference between wavelengths λ 1 and λ 2 . However, since the two lasers are not synchronized, both frequency and phase should be stabilized and the spectral distance between the two laser lines has to be kept fixed, to assure low jitter and low phase-noise [50]. Some of the most popular alternative techniques to achieve this locked spectral behavior include the use of dual-mode lasers [51] or optical frequency comb generators [52], [53].…”
Section: B Thz Communicationsmentioning
confidence: 99%